Evaluation of Pulse Transit Time for Different Sensing Methodologies of Arterial Waveforms - Ghalib Muhammad Waqas Janjua; Dewar Finlay; Daniel Guldenring; Atta Ul Haq; James McLaughlin (IEEE Access, 2023)
We perform a novel comparative analysis between optically and mechanically derived pulse transit time (PTT) that is universally employed technique for cuffless blood pressure (BP) estimation. For data collection two inline photoplethysmogram (PPG) sensors were mounted at the distal and proximal phalanxes of the index finger of each subject and top each PPG sensor fixture a finger ballistocardiogram (BPP) sensors were clamped. The clamped stacking of the BPP sensors over the PPG sensors provided vertical aligned acquisition of the blood flow waveform through the radial artery for both sensors. The analysis of variance (ANOVA) between PTT derived from the BPP and PPG sensors resulted in a statistically significant difference at $p < 0.05$ . The PTT derived from the BPP sensors showed higher values,17.8 milliseconds on average, than the PTT derived from the PPG sensors. Higher accuracy PTT values will improve the estimation of cuffless BP and thus has the potential to revolutionize the technology.